1977
DOI: 10.1111/j.1476-5381.1977.tb16748.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF Δ9‐TETRA‐HYDROCANNABINOL ON BODY TEMPERATURE AND BRAIN AMINE CONCENTRATIONS IN THE RAT AT DIFFERENT AMBIENT TEMPERATURES

Abstract: I Rats were injected intravenously with 2 mg/kg (-)-trans-A9-tetrahydrocannabinol (A9-THC) at ambient temperatures of 40, 2 10, 310 and 370C. 2 The general behaviour exhibited by rats treated with A9-THC was similar at all four ambient temperatures.3 Body temperatures were recorded continuously before and after drug administration. At 40 and 210C, A9-THC caused hypothermia whereas no change in body temperature occurred at 310 and 370C. 4 The concentrations in the whole brain of noradrenaline (NA), dopamine, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…The cannabinoid CB 1 inverse agonist rimonabant antagonized the hypothermic responses to all drugs tested. Our body temperature results agree with previous work using THC (e.g., Fennessy and Taylor, 1977; Pertwee and Tavendale, 1977; Taffe et al, 2015) and other synthetic cannabinoids (De Fry et al, 2004; Fan et al, 1994; Ovadia et al, 1995; Rawls et al, 2002; Tai et al, 2015). In particular, the present temperature data in rats are similar to those reported by Banister et al (2015) who showed that JWH-018, AM2201 and XLR-11 produce robust hypothermia in conscious rats fitted with biotelemetry transmitters (Banister et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The cannabinoid CB 1 inverse agonist rimonabant antagonized the hypothermic responses to all drugs tested. Our body temperature results agree with previous work using THC (e.g., Fennessy and Taylor, 1977; Pertwee and Tavendale, 1977; Taffe et al, 2015) and other synthetic cannabinoids (De Fry et al, 2004; Fan et al, 1994; Ovadia et al, 1995; Rawls et al, 2002; Tai et al, 2015). In particular, the present temperature data in rats are similar to those reported by Banister et al (2015) who showed that JWH-018, AM2201 and XLR-11 produce robust hypothermia in conscious rats fitted with biotelemetry transmitters (Banister et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…The results of the present study agree with previous reports that showed a dose‐dependent reduction in body temperature following Δ 9 ‐THC administration in rats. Similar hypothermic responses have been shown in a number of studies using various cannabinoid CB 1 receptor agonists (Fennessy & Taylor, 1977; 1978; Lichtman & Martin, 1991; Compton et al , 1992; 1996). Δ 9 ‐THC in the same doses and the same species of rat were used by Fennessy & Taylor (1978) as in the present study.…”
Section: Discussionsupporting
confidence: 73%
“…Most previous THC studies used ambient temperatures of 20–22°C in contrast to the present ambient temperatures that averaging 26°C and 23°C, respectively, in Experiments I and II. The influence of ambient temperature on THC-induced thermal responses has been shown in earlier studies that noted the occurrence of a hypothermic response when the experiment was conducted at 10°C or 20°C but not at 31°C (Bloom and Kiernan, 1980; Fennessy and Taylor, 1977). Morley and coworkers (2004) previously reported that concurrent administration of either THC or the synthetic cannabinoid receptor agonist CP 55,940 prevented MDMA-induced hyperthermia.…”
Section: Discussionmentioning
confidence: 78%